BS EN 50117-9-1. Coaxial cables. Part 9-1. Sectional specification for coaxial cables for analogue and digital signal transmission. Indoor drop cables for systems operating at 5 MHz. 1 000 MHz (27th November 2020) - British Standards Institution,
No abstract available